KEGIATAN KAMPUS MENGAJAR TERHADAP MOTIVASI MENJADI GURU BAGI MAHASISWA PESERTA KAMPUS MENGAJAR - Muhammad Ramadhan Putra; Nurjannah; Rijal (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This study aims to determine the influence of teaching campus activities on the motivation to become teachers for teaching campus students of the Faculty of Teacher Training, Muslim Nusantara Alwashliyah University of Medan in 2023/2024. This study used students or participants from teaching campus activities as respondents as many as 20 students. The data collection technique in this study uses a questionnaire given to students participating in the teaching campus. Then, the results of the research in accordance with the hypothesis formulated in this study can be accepted as true, because t is calculated ≥ t table or 3.31 ≥ 1.73. So, it can be concluded that there is an influence of teaching campus activities on the motivation to become teachers for teaching campus students at the Faculty of Teacher Training, Muslim Nusantara Alwashliyah University Medan